Gender inequality in European football: Evidence from competitive balance and competitive intensity in the UEFA Men's and Women's Champions League - Aurélien François; Nicolas Scelles; Maurizio Valenti (Economies, 2022)
Competitiveness of sporting contests is key to attract fan interest. However, limited research compared levels of competitiveness in men's and women's sports. This study focuses on the evolution of intra-match competitive balance (IMCB) and competitive intensity (IMCI) in the UEFA Men's and Women's Champions League (UMCL and UWCL). Data were initially collected for 3299 games over 2001-2019 (2314 in UMCL; 985 in UWCL) to analyse the evolution within and between each tournament. In addition, 989 matches played in UMCL over 1955-1973 were added to compare both competitions in their early stages. Results show a deterioration in IMCB and IMCI between 2001-2009 and 2009-2019 for the UMCL. Conversely, the UWCL benefitted from an increase in IMCB but not in IMCI, except for the final. The UWCL is still less competitive than the UMCL. This result holds true even when comparing the early stages of both competitions, i.e., replacing 2001-2019 by 1955-1973 for the UMCL. However, the UWCL has become closer to the UMCL in terms of IMCB and IMCI over time, a result linked to the development of women's football. From a theoretical perspective, this article advances knowledge of IMCB and IMCI, appropriate for competitions with knockout stages. It underlines the role of the pool of players as an explanatory factor for the gap in competitiveness between European men's and women's football.
Keywords: 330; competition format; competitiveness; men's football; uncertainty of outcome; women's football